AvrPm2 encodes an RNase‐like avirulence effector which is conserved in the two different specialized forms of wheat and rye powdery mildew fungus. Issue 3 (9th December 2016) - Praz, Coraline R.; Bourras, Salim; Zeng, Fansong; Sánchez‐Martín, Javier; Menardo, Fabrizio; Xue, Minfeng; Yang, Lijun; Roffler, Stefan; Böni, Rainer; Herren, Gerard; McNally, Kaitlin E.; Ben‐David, Roi; et al.
Summary: There is a large diversity of genetically defined resistance genes in bread wheat against the powdery mildew pathogen Blumeria graminis ( B. g .) f. sp. tritici . Many confer race‐specific resistance to this pathogen, but until now only the mildew avirulence gene AvrPm3 a2/f2 that is recognized by Pm3a/f was known molecularly. We performed map‐based cloning and genome‐wide association studies to isolate a candidate for the mildew avirulence gene AvrPm2 . We then used transient expression assays in Nicotiana benthamiana to demonstrate specific and strong recognition of AvrPm2 by Pm2 . The virulent AvrPm2 allele arose from a conserved 12 kb deletion, while there is no protein sequence diversity in the gene pool of avirulent B. g. tritici isolates. We found one polymorphic AvrPm2 allele in B. g. triticale and one orthologue in B. g. secalis and both are recognized by Pm2 . AvrPm2 belongs to a small gene family encoding structurally conserved RNase‐like effectors, including Avr a13 from B. g. hordei, the cognate Avr of the barley resistance gene Mla13 . These results demonstrate the conservation of functional avirulence genes in two cereal powdery mildews specialized on different hosts, thus providing a possible explanation for successful introgression of resistance genes from rye or other grass relatives to wheat. Abstract : See also the Commentary on this article by Spanu, 213: 969–971 .